Benzimidazole derivatives protect against cytokine-induced apoptosis in pancreatic β-Cells. Issue 20 (15th October 2015) - Zawawi, Nik Khairunissa Nik Abdullah; Rajput, Sajid Ali; Taha, Muhammad; Ahmat, Norizan; Ismail, Nor Hadiani; Abdullah, Noraishah; Khan, Khalid Mohammed; Choudhary, M. Iqbal
Graphical abstract: Abstract: Apoptotic cell death is the cause of the loss of insulin-producing β-cells in all forms of diabetes mellitus. The identification of small molecules capable of protecting cytokine-induced apoptosis could form the basis of useful therapeutic interventions. Here in, we present the discovery and synthesis of new benzimidazole derivatives, capable of rescuing pancreatic β-cells from cytokine-induced apoptosis. Three hydrazone derivatives of benzimidazole significantly increased the cellular ATP levels, reduced caspase-3 activity, reduced nitrite production and increased glucose-stimulated insulin secretion in the presence of proinflammatory cytokines. These findings suggest that these compounds may protect β-cells from the harmful effects of cytokines and may serve as candidates for therapeutic intervention for diabetes.